The Attitude of Sports Faculty Students related to a Skiing Internship - L. Brabiescu Calinescu; C. Fortan; D. Ciocanescu; C. Albina; I. Nanu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The aim of this study was to identify the perception after the participation to a skiing training course of sports faculty students (76 subjects). Using an online questionnaire, students’ present their opinions about this proposed curricular activity. Results suggest that an internship allows students to have a more realistic and practical exposure is a good personal experience with long-term (professional) impact helping them to identify their goals and skills of the future profession. University sports programs that facilitate an effective "on-site" practical experience can have multiple results for the students –specialists in training, sports curriculum programs should offer more options, partnerships and similar practical experiences.